Porphyrinoid Aromaticity Induced by the Interaction between Oxidized and Reduced Pyridine Subunits1. Issue 17 (29th April 2015) - Neya, Saburo; Suzuki, Masaaki; Mochizuki, Tomomi; Hoshino, Tyuji; Kawaguchi, Akira T.
Abstract: The coupling of 3‐hydroxypyridine‐2, 6‐dicarbaldehyde with a tripyrrane‐like precursor bearing a central pyridine ring afforded a new porphyrinoid with two pyridine‐related subunits. The sharp Soret‐like band at 421 nm in the electronic spectrum and the pyrrole NH signal at δ = –2.98 ppm in the NMR spectrum indicated that the product is aromatic with an 18π‐electron circuit. The proton and carbon NMR spectra further suggested that the electron circuit is produced not only by the keto‐enol isomerization of the 3‐hydroxypyridine unit but also by the local hydrogenative dearomatization in the other pyridine unit at the diagonal site. Single‐crystal X‐ray structure analysis revealed that the carbon atom in the latter pyridine unit is indeed dearomatized to exhibit sp 3 character. These observations, taken together, provide a rare example showing that aromaticity of porphyrinoids is accomplished by the cooperative interaction between oxidized and reduced pyridine rings. Abstract : Coupling of 3‐hydroxypyridine‐2, 6‐dicarbaldehyde with a tripyrrane‐like precursor bearing a central pyridine ring afforded a new porphyrinoid with two pyridine‐related subunits Spectroscopic and theoretical analyses demonstrate that the aromaticity of this porphyrinoid is fulfilled by the cooperative interaction between the two pyridinoid rings.